Nivel de cumplimiento de los requisitos para el reconocimiento como mercado saludable del Mercado Centro Comercial de Loja, año 2022 - Carrión Martínez, Omar Alexander (2023)
The certification of a healthy market holds significant academic importance within Loja city. It not only contributes to providing society with healthy and safe food but also serves as a subject of academic research. This study aimed to assess the degree of compliance with the necessary criteria to designate the "Reina del Cisne" Commercial Center Market as a healthy market in the year 2022. Therefore, the objectives established were: to verify the level of compliance with the requirements for recognition as a healthy market in the "Commercial Center Market" of Loja from both an institutional perspective and the perspective of the merchants, and to propose alternative solutions for the process of recognition as a healthy market. In order to achieve these objectives, a descriptive field investigation was conducted, involving the participation of six representatives from different market blocks. The investigation utilized a verification form consisting of 254 items based on the Ecuadorian Technical Standard NTE INEN 2687:2013. In addition, two interviews were conducted involving the administrator of the "Reina del Cisne" Commercial Center Market and the Specialist from Zone 7 Coordination for Health Promotion. The applied method is deductive in nature, as it allowed for the analysis of the market's broader and significant aspects in order to gain a better understanding of the issues at hand and focus on achieving the set objectives. Among the main results, the level of compliance with the requirements within the market was verified from both the institutional and merchant perspectives. A compliance rate of 73% was achieved across the 12 requirements, highlighting several shortcomings that need to be addressed within the market blocks. Subsequently, a proposal was developed, presenting alternative solutions to improve compliance with each requirement, along with a schedule of activities to be followed. The aim is to reach the desired goal of certification and recognition as a healthy market through the active participation of all merchants and administrative staff within the "Reina del Cisne" Commercial Center Market.